Increased Frequency of Defecation (Acute Diarrhea) in Children Under Five Years of Age in the Antang Health Center Working Area - Arda, Darmi; Pannyiwi, Rahmat; Harfika, Meiana; Dewi, Chitra; Setyaningsih, Rahayu; Nursiah, Andi; Sumampouw, Oksfriani Jufri (International Journal of Health Sciences, 2024)
Diarrhea is a condition in which the frequency of bowel movements becomes abnormal, which is usually 1 x a day, to more than 3 x a day with a liquid stool consistency and usually accompanied by mucus and blood. The purpose of this study was to determine the characteristics of toddlers with acute diarrhea at the Antang Health Center. This type of research is descriptive research using a cross-sectional approach, the results of which are only an illustration. Statistical analysis was conducted to describe the characteristics of each patient using descriptive frequency test. The results of the study prove that exclusive breastfeeding contains antibodies needed to defend against pathogens in toddlers suffering from acute diarrhea at the Antang Health Center, the majority of whom are female, aged 1-2 years, have a history of exclusive breastfeeding, with a last education of junior high school and low family income. It is hoped that this study will be a source of information for the local Health Office and Health Center to reduce the incidence of acute diarrhea.